Exploring pregnancy-related stigma experiences among adolescents in rural Uganda - Koichi Sakakibara; Sarah McIvor Murray; Ethan Godwills Arima; Caesar Ojuka; Itziar Familiar-Lopez (wiley, 2024)
Introduction: Pregnant adolescents face multiple adverse experiences that vary by context due to pregnancy‐related stigma. We explored experiences of pregnancy‐ related stigma and psychosocial issues among adolescents living in rural eastern Uganda. Methods: We conducted in‐depth semi‐structured interviews with 15 adolescents (15–19 years old) who were pregnant (>3 months) or had recently given birth (<3 months) at Tororo District Hospital in Uganda. All interviews were translated from Dhopadhola to English. Thematic analysis was conducted to identify major themes, which were interpreted using the Health Stigma and Discrimination Framework. Results: Six key themes were identified and were organized under the Health Stigma and Discrimination Framework. Social and gender norms for adolescent women and their lack of autonomy were identified as drivers and facilitators of pregnancy‐related stigma. Results show how stigma is experienced by adolescents through the lack of social support, multiple forms of abuse, and negative judgement. Such manifested stigma negatively impacted their psychosocial wellbeing and resulted in limited access to socioeconomic resources and educational opportunities. Conclusion: This study acknowledges the multilevel nature of pregnancy‐related stigma among adolescents in the context of existing policy and programming. Recognizing the impact of pregnancy‐related stigma on the health and wellbeing of adolescent girls necessitates prioritizing comprehensive stigma reduction interventions that address main drivers and facilitators, and that are rooted in the communities to harness support.
Keywords: adolescent pregnancy; education; intimate partner violence; stigma; Uganda